2011
DOI: 10.1002/pi.3176
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the actuation performance of dielectric triblock copolymers modified with additives

Abstract: To enhance actuation performance without prestrain, an elastomeric acrylic triblock copolymer, poly(methyl methacrylate)block-poly(n-butyl acrylate)-block-poly(methyl methacrylate), was modified with two kinds of additives, oligomeric poly(n-butyl acrylate) and the plasticizer dibutyl sebacate. An actuator modified with those additives showed about 6% strain, whereas the unmodified actuator showed only 1% strain for the same applied electric field without prestrain. In addition, actuation was attained at lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Low voltage actuators can be in principle achieved with soft elastomers. They can be prepared either by reducing the cross‐linking density, using plasticizers, synthesizing bimodal heterogeneous networks, or incorporating bottlebrush segments into the polymer network . However, the dielectric breakdown of such soft elastomers is a hurdle still to be overcome .…”
Section: The Amount Of Reagents Used For the Synthesis Of Thin Filmsmentioning
confidence: 99%
“…Low voltage actuators can be in principle achieved with soft elastomers. They can be prepared either by reducing the cross‐linking density, using plasticizers, synthesizing bimodal heterogeneous networks, or incorporating bottlebrush segments into the polymer network . However, the dielectric breakdown of such soft elastomers is a hurdle still to be overcome .…”
Section: The Amount Of Reagents Used For the Synthesis Of Thin Filmsmentioning
confidence: 99%
“…Jang and co‐workers demonstrated that HEX or BCC morphologies, with predominance of the softer block, present higher dielectric constants, in any frequency range studied, when compared to the LAM morphology, formed by alternating layers of the constituent blocks. In order to increase the predominance of the soft block, a strategy has been to prepare BCP physical gels, in which a large concentration of a low molecular weight compound selectively swells the soft block and the phase‐separated microdomains act as physical aggregates . Thus, in addition to increasing the dielectric constant, the gels allow the reduction of stiffness of the block copolymers, since the low molecular weight compound acts as a plasticizer in the system, achieving greater success for application as DEs.…”
Section: Introductionmentioning
confidence: 99%
“…When the reduction of the elastic modulus and the increase of the dielectric constant of these elastomers are achieved, they allow large deformations from an electric field . Among these, block copolymers (BCPs) have promising properties to be used as nanostructured dielectric elastomers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicones Liu, Liu, Zhang & Leng, 2009), acrylics (Jang, Hirai, Ueki & Kato, 2012;Kofod, Sommer-Larsen, Kornbluh & Pelrine, 2003;Pelrine, Kornbluh, Pei & Joseph, 2000) and polyurethanes (Mahapatra, Yadav, Yoo & Cho, 2011;Wongtimnoi, Guiffard, Bogner-Van de Moortèle, Seveyrat, Gauthier & Cavaillé, 2011) are the three most promising groups of DEs, which are all petroleum-based elastomers. To meet the growing demand of environmental protection and resource saving, it is imperative to explore bio-based elastomers as next-generation DE because the bio-based elastomers are available from biomass feedstock.…”
Section: Introductionmentioning
confidence: 99%